2005
DOI: 10.1021/bi051416y
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Lactate Dehydrogenase from Plasmodium vivax:  Complexes with NADH and APADH

Abstract: Malaria caused by Plasmodium vivax is a major cause of global morbidity and, in rare cases, mortality. Lactate dehydrogenase is an essential Plasmodium protein and, therefore, a potential antimalarial drug target. Ideally, drugs directed against this target would be effective against both major species of Plasmodium, P. falciparum and P. vivax. In this study, the crystal structure of the lactate dehydrogenase protein from P. vivax has been solved and is compared to the equivalent structure from the P. falcipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The crystal structure of P. falciparum LDH (Dunn et al 1996) indicated that this five amino acid insertion creates a distinctive cleft in the surface of the enzyme adjacent to the substrate binding site in contrast to the same region of the host LDH. Similar structures were also observed for P. vivax (Chaikuad et al 2005), P. berghei (Winter et al 2003) and T. gondii (Kavanagh et al 2004) LDHs. Several organic molecules have recently been designed and developed with the aim of blocking LDH from P. falciparum (Granchi et al 2010).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The crystal structure of P. falciparum LDH (Dunn et al 1996) indicated that this five amino acid insertion creates a distinctive cleft in the surface of the enzyme adjacent to the substrate binding site in contrast to the same region of the host LDH. Similar structures were also observed for P. vivax (Chaikuad et al 2005), P. berghei (Winter et al 2003) and T. gondii (Kavanagh et al 2004) LDHs. Several organic molecules have recently been designed and developed with the aim of blocking LDH from P. falciparum (Granchi et al 2010).…”
Section: Discussionsupporting
confidence: 80%
“…This enzyme catalyses the interconversion of pyruvate and l-lactate with a concomitant interconversion of NADH and NAD + (Holbrook et al 1975). On the basis of molecular cloning studies, kinetic characterisations and X-ray structure analysis, plasmodial LDH's have been studied in most detail (Dunn et al 1996;Turgut-Balik et al 2001a;Chaikuad et al 2005) among the apicomplexan parasites and have been identified as new enzyme targets for the development of novel antimalarial drugs. Determination of the key residues in the active site of this enzyme from Plasmodium showed that this site could be an attractive target for enzyme inhibitors (Dunn et al 1996;Turgut-Balik et al 2001b).…”
mentioning
confidence: 99%
“…among apicomplexan parasites [16] . Because Plasmodium species do not have a functional Krebs cycle, as Thelieria species, they produce their energy via glycolysis [17,18] .…”
Section: Comparison Of T Annulata and Bos Taurus Eno's By Homology Mmentioning
confidence: 99%
“…Because Plasmodium species do not have a functional Krebs cycle, as Thelieria species, they produce their energy via glycolysis [17,18] . Lactate dehydrogenase enzyme has a crucial role in this parasites life as it catalyzes the reduction of pyruvates to hydroxyls by oxidation of NADH to NAD + [16] . It is important to note that, Plasmodial LDH also has a pentapeptide insertion in the active site of the enzyme [19] .…”
Section: Comparison Of T Annulata and Bos Taurus Eno's By Homology Mmentioning
confidence: 99%
See 1 more Smart Citation